ANALYSING STUDENTS’ CRITICAL THINKING, COMMUNICATION, COLLABORATION, AND CREATIVITY SKILLS DURING ANIMAL PHYSIOLOGY COURSES - Isnaeni, Wiwi; Budi Prasetyo, Andreas Priyono; Ristianafi, Diana Putri; Setiawan, Heru (Unnes Science Education Journal, 2019)
Animal Physiology with Project Based Learning (Pj-BL) was created to support 4Cs students’ thinking skills (critical thinking, communication, collaborative and creativity). The study was aimed at qualitatively describing the 4Cs students’ skills. At least 63 ‘odd’ semester and 96 ‘even’ semester Unnes biology students at during the 2018/2019 academic year was involved. Data was collected by observation, interviews, and questionnaires. Qualitative data analysis with triangulation and descriptive qualitative techniques was implemented. Finding showed 4Cs student skills were significantly indentified during (1) the material briefings, (2) developing project proposals, (3) conducting research, writting a written report, enriching material and (4) orally sharing the findings.